Disfunción inmunometabólica en el VIH: bases epistemológicas - Gutiérrez-Salas , A. A.; Delgadillo-Guzmán, D.; Hernández-Silva, M.; López-Márquez , F. C. (Revista de Ciencias Médicas Torreón, 2026)
The relationship between metabolic syndrome and proinflammatory cytokines in people living with HIV has not been conclusively established. It is suggested that chronic inflammation, derived from viremia and metabolic alterations, could explain this association. This article proposes an epistemological reflection aimed at strengthening scientific understanding and the application of bioethics in future epidemiological research. Materials and methods: A qualitative study was conducted with a hermeneutic and epistemological approach. A documentary and critical analysis of scientific articles, systematic reviews, and regulatory documents related to HIV, cytokines, and metabolic syndrome was performed. Results: The analysis allowed us to identify patterns and ethical and epistemological implications in the reviewed literature. The ideas of David Hume on experience-based knowledge and Bradford Hill on the criteria of causality in epidemiology are taken up as references for the construction of scientific knowledge. In conclusion, the integration of philosophical and bioethical thought into medical research allows us to reinterpret knowledge from a humanistic perspective, recovering lessons from the past to guide science toward a more reflective, ethical, and socially responsible practice